Softball bat inertial considerations and their effects on female softball swing mechanics and estimated bat performance - Nesbit, S. M.; Milanovich, M. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
This paper discusses the role of the inertial properties in the design and selection of the softball bat, and their interrelated effects on female softball swing mechanics and bat performance. The study was performed using 14 collegiate subjects whose swings were analyzed via a computer model, which included methods for estimating post-impact ball velocity. The model was driven kinematically by subject swing recordings using two different trial bats with markedly different inertial properties. Using this method, the following information was determined: subjects altered their linear kinetic inputs while applying consistent angular kinetic inputs to maintain nearly consistent trajectories; subjects compensated for increased bat inertia by modification of the bat instantaneous center-of-rotation trajectory (ICR); and swing trajectory influenced the bat`s inertial feel, actual, and ideal impact locations, and batted-ball velocity. Subsequently, the mass properties of 27 collegiate level bats were input into the model for each subject trial. Using this information, the relative changes in kinetic inputs were quantified and the performance of the bats was estimated. Results showed that bat inertial properties varied considerably, and independent manipulation of individual properties was evident. In addition, subject kinetic inputs and bat performance measures were most affected by changes in mass center (CG) location, mass, and CG inertia. A modified definition of IGRIP based upon the ICR was presented, and practical implications for designers and practitioners were offered based upon these findings.